Perencanaan Strategis Pariwisata Budaya: Mekanisme Menuju Pariwisata Berkelanjutan (Jurnal Ilmiah Pariwisata; Vol 19 No 1 (2014), 2014)
There is a consensus among tourism stakeholders in a destination that strategic planning is vital to guide them in designing and implementing tourism programs. Literature has also described the significance of strategic planning in achieving the goal of tourism development of an organization or institution. However, little explanation is available on the link between strategic planning and sustainable cultural tourism. This paper is a critical review of literature focusing at the significance and mechanism of strategic planning for sustainable cultural tourism. Sustainability is the most familiar approach used and mentioned in strategic plans. It is a desirable goal of tourism planners and stakeholders and thus, its principles are used as driver in designing strategic planning. This paper suggests that strategic plan should be used as a guide rather than just an official document. Cultural tourism requires careful management and thus, it is necessary to create strategic planning on the basis of sustainable principles.
Keywords: Strategic planning, Cultural tourism, Sustainability, Sustainable tourism